Handbook of methadone prescribing and buprenorphine therapy - Knotkova, Helena; Cruciani, Ricardo A. (Springer New York, 2013)
Methadone and buprenorphine are the only two opioids that are indicated for the management of both pain and opioid-related drug addiction.  Both present unique challenges to the general practitioner and pain specialist, requiring a separate analysis from the rest of the drugs in the same family.  Handbook of Methadone Prescribing and Buprenorphine Therapy is an invaluable guide to the safe use of these opioids.  Authored by clinical and academic leaders from a variety of settings and backgrounds, this book includes chapters on pharmacology, adverse effects, safe rotation from other opioids, cardiac toxicity, prescribing, pharmacokinetics, equianalgesic dose, and replacement therapy. This comprehensive text provides clinicians, researchers, policy-makers and academicians a resource for all the relevant points in methadone prescribing and buprenorphine therapy.